Numerical Calibration of Electric Field Probe for Specific Absorption Rate Measurement - Agarwal M.; Monebhurrun V. (My University, 2025)
An experimental setup is traditionally used to calibrate the electric (E) field probe used for the specific absorption rate (SAR) measurement of wireless communication devices. Numerical simulation is herein proposed to perform the calibration of the E-field probe. The numerical approach is validated with known calibration data at several frequencies. The unknown calibration factor at a given frequency is deduced and the corresponding SAR of the wireless communication device measured. © 2019 IEEE.